1991
DOI: 10.1111/j.1476-5381.1991.tb12201.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide and human epicardial coronary arteries: presence, release and vasodilator effects

Abstract: 1 In the present study, the levels of calcitonin gene-related peptide (CGRP)-like immunoreactivity (-LI) in human cardiopulmonary tissue were determined in combination with studies on CGRP-LI release from the left anterior descending coronary artery (LAD) and functional effects of CGRP on coronary arterial tone.2 The highest levels of CGRP-LI were found in the LAD followed in declining order by the bronchus, right atrium, pulmonary artery, lung and left ventricle. 3 Exposure to capsaicin evoked a clear-cut i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
20
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 36 publications
9
20
1
Order By: Relevance
“…cardiovascular system (196)(197)(198)(199) and the presence of i-CGRP in perivascular nerves (1), taken together with the potent vasodilatory activity of CGRP (237-256), suggest that this peptide may play a major role in regulating peripheral vascular tone and controlling blood flow in various organs (12). The highest concentrations of i-CGRP in human cardiopulmonary tissues are found in the left anterior descending artery, whose relaxation is independent of activation of endothelium-derived-relaxant factor (EDRF) nitric oxide (251). Direct infusion of CGRP into large coronary arteries, including the left anterior descending artery, did not cause a change in blood pressure or heart rate, although it significantly reduced coronary artery resistance and increased coronary blood flow (256)(257)(258)(259).…”
Section: B Distribution Of Cgrp Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…cardiovascular system (196)(197)(198)(199) and the presence of i-CGRP in perivascular nerves (1), taken together with the potent vasodilatory activity of CGRP (237-256), suggest that this peptide may play a major role in regulating peripheral vascular tone and controlling blood flow in various organs (12). The highest concentrations of i-CGRP in human cardiopulmonary tissues are found in the left anterior descending artery, whose relaxation is independent of activation of endothelium-derived-relaxant factor (EDRF) nitric oxide (251). Direct infusion of CGRP into large coronary arteries, including the left anterior descending artery, did not cause a change in blood pressure or heart rate, although it significantly reduced coronary artery resistance and increased coronary blood flow (256)(257)(258)(259).…”
Section: B Distribution Of Cgrp Receptorsmentioning
confidence: 99%
“…Spasm of coronary arteries may occur in association with atheromatous disease, in isolation, or in combination with variant or Prinzmetal's angina (425). In vitro studies have shown that CGRP can rapidly relax human epicardial coronary arteries that have been previously constricted with serotonin (423). Like nitrates, CGRP also relaxes human coronary arteries directly, without mediation of endothelium-derived growth factors (537).…”
Section: Therapeutic Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in CGRP levels cannot be explained by the lack of a pulmonary circulation during CPB, as there was no significant difference between arterial and venous levels. The coronary arteries contain 10 times more CGRP than peripheral arteries [25]. However, as their blood flow constitutes only 5% of cardiac output, the peripheral arteries can be thought of as the main production site of CGRP [26].…”
Section: Discussionmentioning
confidence: 99%